β-Caryophyllene promotes osteoblastic mineralization, and suppresses osteoclastogenesis and adipogenesis in mouse bone marrow cultures in vitro - Yamaguchi, Masayoshi (Exp Ther Med, 2016)
Osteoporosis is induced by the reduction in bone mass through decreased osteoblastic osteogenesis and increased osteoclastic bone resorption, and it is associated with obesity and diabetes. Osteoblasts and adipocytes are derived from bone marrow mesenchymal stem cells. The prevention of osteoporosis is an important public health concern in aging populations. β-caryophyllene, a component of various essential oils, is a selective agonist of the cannabinoid receptor type 2 and exerts cannabimimetic anti-inflammatory effects in animals. The present study aimed to identify the effect of β-caryophyllene on adipogenesis, osteoblastic mineralization and osteoclastogenesis in mouse bone marrow cell cultures in vitro. Bone marrow cells obtained from mouse femoral tissues were cultured in the presence of β-caryophyllene (0.1–100 µM) in vitro. The results revealed that β-caryophyllene stimulated osteoblastic mineralization, and suppressed adipogenesis and osteoclastogenesis. Thus, β-caryophyllene may be used as a therapeutic agent for the prevention and treatment of osteoporosis.